2007
DOI: 10.1016/j.ajo.2006.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Select Redox Proteins of the Retinal Pigment Epithelium in Age-related Macular Degeneration

Abstract: PURPOSE-To examine changes of select reduction-oxidation (redox) sensitive proteins from human donor retinal pigment epithelium (RPE) at four stages of age-related macular degeneration (AMD). DESIGN-Experimental study.METHODS-Human donor eyes were obtained from the Minnesota Lions Eye Bank and graded using the Minnesota Grading System (MGS) into four stages that correspond to stages defined by the age-related eye disease study (AREDS). Protein content in RPE homogenates was measured using Western immunoblottin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
107
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 70 publications
6
107
0
Order By: Relevance
“…Increased Hsp27 protein content along with evidence of cellular oxidative stress was reported in human eyes with AMD, but Hsp27 phosphorylation was not investigated. 50 Our findings provide novel evidence that phosphorylated Hsp27 may play a major role in the pathogenesis of AMD. In response to stress, phosphorylated Hsp27 undergoes conformational changes and reorganizes into dimeric units.…”
Section: Hsp27 and Oxidative Stress In Rpe 1209mentioning
confidence: 74%
“…Increased Hsp27 protein content along with evidence of cellular oxidative stress was reported in human eyes with AMD, but Hsp27 phosphorylation was not investigated. 50 Our findings provide novel evidence that phosphorylated Hsp27 may play a major role in the pathogenesis of AMD. In response to stress, phosphorylated Hsp27 undergoes conformational changes and reorganizes into dimeric units.…”
Section: Hsp27 and Oxidative Stress In Rpe 1209mentioning
confidence: 74%
“…15 Hence, there is only weak epidemiologic evidence that excessive exposure to light is associated with AMD. 16,17 Furthermore, chronic excessive exposure to light increases the risk of cataract formation, 18 this might be a form of natural protection for the retina. With the advances in cataract surgery, surgery is often preformed at an earlier age.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…A direct correlation with upregulation of this antioxidant pathway is seen with the different stages of AMD. 18 There is currently no therapeutic application for the enzymes themselves, however, they are reliant upon enzyme cofactors such as zinc and copper.…”
Section: Compartmentalisationmentioning
confidence: 99%
“…Recently, Shen et al reported a direct demonstration of increased oxidative stress in the retinas of AMD eyes with geographic RPE atrophy [39]. Additionally, changes in select RPE redox proteins have been reported in AMD eyes and oxidized phospholipids in the macula have been reported to increase with age and in eyes with AMD [40,41]. Moreover, isolation of microgram quantities of drusen identified a high concentration of oxidatively-modified proteins in AMD eyes [42].…”
Section: Er Stress In Amdmentioning
confidence: 99%
“…Among these were several molecular chaperones whose expression decreased with AMD progression, including Hsp60 and HOP [16]. Additionally, several antioxidant enzymes and chaperones that facilitate refolding or degradation of oxidatively damaged proteins decreased in AMD eyes: copper-zinc superoxide dismutase, manganese superoxide dismutase, catalase, and Hsp27, Hsp 90, and proteasome [40]. Moreover, human AMD lesions and retina from the Ccl2/Cx3cr1 deficient murine model of AMD were reported to exhibit decreased mRNA and protein expression of ERp29, a protein escort and folding chaperone [18].…”
Section: Er Stress In Amdmentioning
confidence: 99%